IMPLEMENTASI FUNGSI PEMBINAAN DAN PENGAWASAN KEPADA PEJABAT PEMBUAT AKTA TANAH (Studi Kabupaten Deli Serdang) - IRHAM KOSIM (PREMISE LAW JURNAL, 2017)
ABSTRACT Official empowered to draw up land deeds (henceforth he is called PPAT) is an official who helps the National Land Agency (henceforth it is called BPN) as the agency that is responsible for registering land. A PPAT is one of the public officials (ambtenaar) who needs development and supervision in doing his job as an official who empowers to draw up land deeds. The function of developing and supervising PPAT is done by the BPN of Deli Serdang Regency according to legal provisions by directly visiting PPAT offices and not registering the land in the BPN of Deli Serdang in doing its development and supervision. Keywords: Function of Development and Supervision, Official Empowered to Draw up Land Deeds, Deli Serdang Regency